Pengendalian Persediaan Bahan Baku dengan Model Sistem Dinamik (Studi Pada Perusahaan Furniture) - Albertus Magnus Madyana (Universitas Bunda Mulia, 2017)
Efficiency and effectivity enhancement is a problem of every company. Material stocks optimization is an effort for this problem, and it can be done by choosing the best system, when the material be used for production and needed to control material stocks. The purpose of this study is to analyze inventory problem using dynamic system simulation (Powersim). The application of some scenarios results in references as a policy formula in considerations. In the research case at Furniture Corporation, by applying material order interval change scenario, the result is a saving of cost of total production by 5,808 %.Keywords: Dynamic System Simulation, Material Stocks Optimization, Order Interval